Effects of muscarinic acetylcholine receptor stimulation on the differentiation of mouse induced pluripotent stem cells into neural progenitor cells. (26th July 2018) - Ishizuka, Toshiaki; Ozawa, Ayako; Katsuura, Mieko; Nomura, Sayaka; Satoh, Yasushi
Summary: Muscarinic acetylcholine receptors (mAchRs), which are expressed in various embryonic cells, may regulate neuronal differentiation. In the present study, we examined the effects of mAchR stimulation on the differentiation of mouse induced pluripotent stem (iPS) cells into neural progenitor cells (NPCs). Mouse iPS cells were cultured on ultra‐low attachment dishes to induce embryoid body (EB) formation. All‐trans retinoic acid (ATRA, 3 μmol/L) and/or pilocarpine (10 or 100 μmol/L), a mAchR agonist, were added to EB cultures for 4 days, following which the EBs were cultured on gelatin‐coated plates for 7 days. Subtype‐specific antibody staining revealed that mouse iPS cells predominantly express m2 ‐ and m4 ‐AchR. Treatment with pilocarpine alone did not affect the expression of Nestin (a specific marker for neural progenitor cells). However, additional treatment with pilocarpine significantly suppressed ATRA‐induced Nestin expression. Pretreating EBs with either AF‐DX116 (an antagonist of both m2 ‐ and m4 ‐AchR) or forskolin (an activator of adenylate cyclase) significantly reversed the pilocarpine‐induced suppression of Nestin expression. In addition, treatment with pilocarpine significantly suppressed ATRA‐induced phosphorylation of cyclic adenosine monophosphate (cAMP) response element‐binding protein (CREB). These findings suggest that the stimulation of m2 ‐ or m4 ‐AchR suppresses ATRA‐induced differentiation of mouse iPS cells into NPCs by inhibiting the cAMP/protein kinase A pathway and CREB activation.